Teaching Vocabulary Using Games: A Case Study of ELT Classroom at 7th Grade Students of Secondary School - Mikhael Misa (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effectiveness of using games to teach vocabulary. To determine the effectiveness of researchers comparing learning outcomes using conventional methods with learning outcomes using games. The method used was experimental research which consisted of an experimental group and a control class consisting of 20 students each in the seventh grade of Middle School. The four types of tests are multiple-choice, word matching, and true-fall tests. To analyze the data, the researcher used the Standard Deviation. Calculation of t-score is 132 > 0.44. Compared to the t-table, the t-score is higher. Thus, this shows that there is effectiveness in teaching vocabulary by using games. As a result, using games to teach vocabulary can improve students' vocabulary mastery. This proves that students' mastery of teaching vocabulary using games is significant. Developing student success requires a good partnership, between the teacher and the students themselves.